An Assessment of the Financial Reporting Practices of Listed Philippine Banks in 2003 - Cayanan, Arthur S (Philippine Management Review; Vol 11 (2004), 2016)
This article shows the results of the assessment of the listed Philippine banks' financial reporting practices as regards their compliance with the financial reporting requirements embodied in the Securities Regulation Code Rule 68 and 68.1 and the Statements of Financial Accounting Standards. The findings show that the banks' financial reporting practices still leave much to be desired.  Among the violations include questionable accounting policies which led to overstatement of  reported net income, lack of adequate disclosures on guarantees and segment information and non-presentation of amounts expected to be received and due within a year in an unclassified balance sheet